Peran Pendidikan Agama Islam Dalam Mengatasi Degradasi Moral Sebagai Respon Perkembangan Era Disrupsi - Moch Jamilul Latif; Singgih Shodiqin; Alaika M. Bagus Kurnia PS. (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
Education in the era of disruption is being faced with the problem of moral degradation, o ne of which is the impact of social media, therefore it is hoped that Islamic religious education on the one hand can overcome it and on the other hand be able to meet the needs of the world by producing a quality generation. This study aims to determine the concept of Islamic education from the perspective of the figures, to find out how much influence social media has on moral degradation, to determine the strategy of Islamic religious education in overcoming moral degradation. This research is grouped in library research with data collection techniques in the form of books and journals and using data analysis techniques using descriptive analysis methods, content analysis, and critical analysis. The results of the study explain that the concept of Islamic religious education emphasizes quality according to universal needs. From a negative point of view, social media has a great influence on moral degradation because of the content that is served without any filters. The strategy of Islamic religious education in overcoming moral degradation in this era of disruption involves the family environment, schools, educators, and the community in strengthening religion.